2017
DOI: 10.1590/s1806-37562016000000051
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing in patients with COPD and mild hypoxemia: prevalence and predictive variables

Abstract: Objective:To infer the prevalence and variables predictive of isolated nocturnal hypoxemia and obstructive sleep apnea (OSA) in patients with COPD and mild hypoxemia.Methods:This was a cross-sectional study involving clinically stable COPD outpatients with mild hypoxemia (oxygen saturation = 90-94%) at a clinical center specializing in respiratory diseases, located in the city of Goiânia, Brazil. The patients underwent clinical evaluation, spirometry, polysomnography, echocardiography, arterial blood gas analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The normal range for PaO 2 was defined as PaO 2 >80 mmHg; mild hypoxia was defined as 60 mmHg<PaO 2 ≤ 80 mmHg [18]. The normal range for SaO 2 was defined as SaO 2 >94%; mild hypoxia was defined as 90% ≤ SaO 2 ≤ 94% [19].…”
Section: Methodsmentioning
confidence: 99%
“…The normal range for PaO 2 was defined as PaO 2 >80 mmHg; mild hypoxia was defined as 60 mmHg<PaO 2 ≤ 80 mmHg [18]. The normal range for SaO 2 was defined as SaO 2 >94%; mild hypoxia was defined as 90% ≤ SaO 2 ≤ 94% [19].…”
Section: Methodsmentioning
confidence: 99%
“…Two studies, one using an AHI cut-off ≥ 5events/hr with symptoms [13] and one > 10events/hr [15] found a significantly increased risk of hypertension in the overlap population compared to the COPD population [OR=2.42, 95%CI 1.58-3.69) and OR 2.56, 95%CI 1.18-5.57 respectively]. While a remaining five studies [18,20,21,31,32] found no significant difference. Only one study investigated cardiovascular mortality [15] and found a significantly increased risk in patients with overlap compared to COPD patients (OR=2.81, 95%CI 1.40-5.64).…”
Section: Comparison Of Cardiovascular Outcomes Between Patients With ...mentioning
confidence: 99%
“…A total of 17 studies [11][12][13][14][15][16][17][18][19][20][21][22]29,[31][32][33][34] (n= 4580) looked at the prevalence of hypertension in the overlap population (Figure S2). Studies were heterogenous in terms of their AHI cut-off, with eight studies [11,12,16,17,22,29,33,34] using AHI ≥ 5events/hr (n=2000, pooled prevalence 57%, 95%CI 44%-71%); two [13,14] using AHI ≥ 5events/hr with symptoms (n=210, pooled prevalence 74%, 95%CI 68%-79%); two [15,21] using AHI > 10events/hr (n= 89, pooled prevalence 50%, 95%CI, 39%-60%); four [18][19][20]31] using AHI ≥ 15events/hr (n= 2267, pooled prevalence 60%, 95%CI 49%-71%) and one [32] using AHI ≥ 30events/hr (n= 14, pooled prevalence 64%, 95%CI 51%-66%).…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with healthy control subjects, poor sleep quality is more frequent in COPD patients. The prevalence of sleep-disordered breathing is reported to be between 50% and 60% in patients with COPD [7,8]. The most common symptoms include sleep onset insomnia, nighttime awakenings, and sleep deprivation [9,10].…”
Section: Introductionmentioning
confidence: 99%